IN LOVING MEMORY OF A GIFTED HISTORIAN, PROF. EMERITUS DATUK DR. AHMAT ADAM, 1941-2025 - Sivachandralingam Sundara Raja (SEJARAH: Journal of the Department of History, 2025)
IN LOVING MEMORY OF A GIFTED HISTORIAN, PROF. EMERITUS DATUK DR. AHMAT ADAM, 1941-2025